First Case in Italy of Fatal Intoxication Involving the New Opioid U-47700 - Gerace, Enrico; Salomone, Alberto; Luciano, Clemente; Di Corcia, Daniele; Vincenti, Marco (Frontiers in Pharmacology, 2018)
The drug commonly known as U-47700 is a strong µ-opioid agonist with an approximate potency 7.5 times higher than morphine. It has been available in Europe since 2014, where it is usually sold through the internet or black market as an abuse morphine-like substance. In the case reported here, a 42-year-old man was found dead in his apartment. Next to the body, the police seized one transparent plastic bag containing a white powder and two amber glass bottles with nasal spray containing few milliliters of a transparent liquid. During the autopsy, no evidence of natural disease or trauma was found to account for the death. Blood, urine and pubic hair were collected and submitted for toxicological analysis. The content of the seized materials was also submitted to a general screening analysis in order to determine its composition. U-47700 was detected in blood, urine and hair samples using an UHPLC/MS-MS method purposely developed. The blood and urine concentrations were 0.38 mg/L and 10.4 mg/L, respectively. No other drugs of abuse nor ethanol were found in blood and urine specimens. Pubic hair analysis revealed a frequent past exposure to U-47700. Finally, U-47700 was identified as the main component of the powder and the liquids contained in the nasal spray bottles. The combined circumstantial elements and toxicological results of the case revealed the occurrence of an acute intoxication produced by U-47700 abuse. To the best of our knowledge, this is the first fatal intoxication case reported on the Italian territory involving the synthetic opioid U-47700.